SAFEGUARDING DIGITAL WEALTH: REDEFINING INVESTOR PROTECTION AGAINST PROTOCOL FRAUDS IN DECENTRALIZED FINANCIAL ECOSYSTEMS - Yossy Andrew Girsang; Udin Silalahi; Ario Setra Setiadi (Kertha Semaya: Journal Ilmu Hukum, 2026)
The rapid expansion of Decentralized Finance (DeFi) in Indonesia has introduced significant risks to market integrity, most notably through the rug pull phenomenon, which exploits the autonomous and pseudonymous nature of blockchain protocols to defraud investors. This research evaluates the efficacy of the current Indonesian regulatory framework, specifically the Financial Services Authority Regulation Number 23 of 2025, in addressing these deceptive practices. Using a normative legal research methodology with statute and comparative approaches, the study juxtaposes the Indonesian oversight model with the European Union’s Markets in Crypto Assets (MiCA) regulation. The findings indicate that while the Indonesian framework provides a solid foundation for centralized trading providers, it remains largely ineffective against truly decentralized protocols that operate without identifiable intermediaries. This creates a critical legal vacuum in terms of investor redress and the determination of liability under existing civil doctrines such as the rule of unlawful acts. Consequently, the research proposes an ideal model for Indonesia by integrating prescriptive MiCA principles, including mandatory standardized white paper disclosures, strict requirements for asset segregation, and the institutionalization of smart contract audits. Such reforms are essential to transitioning from a reactive administrative regime to a proactive and technologically informed shield for investor protection, thereby securing the long term stability of the national digital financial ecosystem.